When the name of philosophy is juxtaposed with Islamic law, the question is how to study and understand Islamic law contemplatively. What to look for and find in Islamic law, how to search and find it, what is it for searched and found? Philosophical unde - Mohammad Fateh (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2013)
When the name of philosophy is juxtaposed with Islamic law, the question is how to study and understand Islamic law contemplatively. What to look for and find in Islamic law, how to search and find it, what is it for searched and found? Philosophical understanding of Islamic law will has an impact on a deeper understanding of Islamic law systematic and logical, by interpreting the philosophy of Islamic law, right? as philosophical material, but rather as Islamic legal material which is studied in detail philosophical. Thus, the critical nature of philosophy is indicated by three approaches in philosophy, namely approaches to ontology, epistemology, and axiology. If philosophy is coupled with Islamic law, then law Islam will be criticized for its essence, source of knowledge and function pragmatics as well as ethics and aesthetics. This article focuses on Hasbi ash Shiddieqiy's main thoughts on Legal Philosophy Islam by criticizing the methodology it uses in equates Islamic legal philosophy with wisdom. In fact, with see the main foundations of philosophy, namely ontology, epistemology, axiology, then Islamic Legal Philosophy covers it as a whole from the scope of fiqh, ushul fiqh, legal secrets, wisdom, and maqashid as shari'ah.